An all-in-one approach for self-powered sensing: a methanol fuel cell modified with a molecularly imprinted polymer for cancer biomarker detection - Carneiro, Liliana (2022)
This work describes the development of an innovative electrochemical biosensor comprehending a passive direct methanol fuel cell (DMFC) assembly, modified by a layer of a molecularly imprinted polymer (MIP) on a carbon fabric anode electrode containing Pt/Ru nanoparticles, This MIP film was prepared from poly(3,4-ethylenedioxythiophene) (PEDOT) and polypyrrole (PPy) obtained by in situ electropolymerization of the corresponding monomers on the anode electrode surface. This MIP film is designed to detect an important cancer biomarker- carcinoembryonic antigen (CEA). This innovative, all-in-one device works in a simple way. First, CEA is incubated on the anode container of the fuel cell, then methanol is added, followed by the response evaluation (polarization curves determination). As CEA selectively interacts with the MIP film, it blocks the methanol's access to the Pt catalyst, remains specific bonded, and interferes with the subsequent polarization curves of the DMFC. Polarization curves obtained in the presence of standard solutions prepared in buffer and human serum confirmed linear responses of log CEA concentration ranging from 30 to 30 000 ng/mL in both media. The biosensor DMFC showed a sensitive response with a detection limit of 4.41 ng/mL when an aqueous 0.05 M methanol solution was used as fuel. When methanol was replaced by an ethanol solution of the same concentration (using the same setup developed for the DMFC), the lower detection limit of 3.52 ng/mL was obtained. Overall, the obtained results show that methanol/ethanol fuel cells operating without flow-through can be successfully used for the fabrication of self-powered biosensors. The novel biosensor concept presented here is simple, inexpensive, and effective, and can be further developed to meet point-of-care requirements.